2016
DOI: 10.1128/jvi.00869-16
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Roles of Double-Stranded RNA Effector Pathways and Viral Defense Proteins Revealed with CRISPR-Cas9 Knockout Cell Lines and Vaccinia Virus Mutants

Abstract: Vaccinia virus (VACV) decapping enzymes and cellular exoribonuclease Xrn1 catalyze successive steps in mRNA degradation and prevent double-stranded RNA (dsRNA) accumulation, whereas the viral E3 protein can bind dsRNA. We showed that dsRNA and E3 colocalized within cytoplasmic viral factories in cells infected with a decapping enzyme mutant as well as with wild-type VACV and that they coprecipitated with antibody. An E3 deletion mutant induced protein kinase R (PKR) and eukaryotic translation initiation factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 69 publications
3
87
0
Order By: Relevance
“…VACV E3 is a multifunctional protein that inhibits other antiviral proteins with dsRNA binding capabilities, including 2 -5 -OAS in the RNaseL pathway, in addition to PKR. [37][38][39] Our findings indicate that PKR is most likely the primary target of E3 in respect to virus replication in the analyzed cells because K3 orthologs that effectively inhibited PKR completely rescued virus replication. While we have not ruled out the possibility that CaPV K3L has evolved to inhibit multiple dsRNA-mediated host restriction factors, on the basis of the known mechanism that orthopoxvirus K3 acts as a PKR pseudosubstrate, this possibility is unlikely.…”
Section: Discussionmentioning
confidence: 72%
“…VACV E3 is a multifunctional protein that inhibits other antiviral proteins with dsRNA binding capabilities, including 2 -5 -OAS in the RNaseL pathway, in addition to PKR. [37][38][39] Our findings indicate that PKR is most likely the primary target of E3 in respect to virus replication in the analyzed cells because K3 orthologs that effectively inhibited PKR completely rescued virus replication. While we have not ruled out the possibility that CaPV K3L has evolved to inhibit multiple dsRNA-mediated host restriction factors, on the basis of the known mechanism that orthopoxvirus K3 acts as a PKR pseudosubstrate, this possibility is unlikely.…”
Section: Discussionmentioning
confidence: 72%
“…This finding was somewhat surprising as F1 has been viewed as an early protein, and many VACV early proteins are expressed in the absence of E3 (17,35). However, a recent report documented that expression of the early D9 mRNA decapping enzyme also requires E3 (39). Currently, it remains unclear why F1 and D9 mRNAs display enhanced sensitivity to translational inhibition by PKR relative to that of other early mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative possibility is that E3 is required for expression of the F1 protein during infection. Although F1 is an early protein (37) and although many early proteins are expressed in the absence of E3 (38), a recent report demonstrated that expression of the early D9 mRNA decapping enzyme requires E3 (39), providing a precedent for E3-dependent early gene expression. We therefore examined the effect of deleting E3 on expression of the F1 protein.…”
Section: F1 Protein Does Not Accumulate During Vacv⌬e3l Infectionmentioning
confidence: 99%
“…Therefore, we postulate that the J2 antibody is principally detecting “free” dsRNA (i.e., not bound by E3) within poxvirus-infected cells. Interestingly, a recent report showed that the J2 antibody could be used to pull-down a E3-GFP fusion protein in an immunoprecipitation assay (Liu and Moss, 2016). The authors used a human cell line at 13 hrs.…”
Section: Discussionmentioning
confidence: 99%